2015
DOI: 10.1002/erv.2404
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Personality Predictors of Weight Loss and Comorbid Metabolic Changes After Bariatric Surgery

Abstract: Bariatric surgery (BS) has proven to be the most effective treatment for weight loss and for improving comorbidities in severe obesity. A comprehensive psychological assessment prior to surgery is proposed to prepare patients for a successful post-surgical outcome. Therefore, the main aim of the present study was to assess psychological and personality predictors of BS outcome. The sample comprised 139 severely obese patients who underwent BS. Assessment measures included the Eating Disorders Inventory-2, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 68 publications
5
43
0
5
Order By: Relevance
“…While these results are not contradictory, they are in opposite directions. Considering that the sample in one of these studies was small 41 and that other articles 12,14,21 did not detect these associations, it can be concluded that there is no consensus in relation to self-transcendence and outcomes of weight reduction or bulimic behavior/vomiting.…”
Section: General Description Of Articles Assessedmentioning
confidence: 92%
See 4 more Smart Citations
“…While these results are not contradictory, they are in opposite directions. Considering that the sample in one of these studies was small 41 and that other articles 12,14,21 did not detect these associations, it can be concluded that there is no consensus in relation to self-transcendence and outcomes of weight reduction or bulimic behavior/vomiting.…”
Section: General Description Of Articles Assessedmentioning
confidence: 92%
“…Three studies 12,33,40 assessed patients beyond 12 months, just one of which conducted follow-up at 36 and 48 months. 40 It is notable that in the context of personality assessment, few studies conducted long-term follow-up of these patients, especially beyond 18 months, when the likelihood of weight gain is higher.…”
Section: General Description Of Articles Assessedmentioning
confidence: 99%
See 3 more Smart Citations